1. расскрываем скобки 2х^2-80=-x^2+6x+24+1
переносим 3х^2-6х-105=0
делим на 3 х^2-2х-35=0
Д=4+140=144
х1=7 х2=-5
2, 1/2xв квадрате -1/2-1/6 *2xв квадрате-5/6х=0
умножаем на 6 3*2xв квадрате-xв квадрате-5х-3=0
2 xв квадрате-5х-3=0
Д=25+24=49
х1=-1,5 х2=3
1. расскрываем скобки 2х^2-80=-x^2+6x+24+1
переносим 3х^2-6х-105=0
делим на 3 х^2-2х-35=0
Д=4+140=144
х1=7 х2=-5
2, 1/2xв квадрате -1/2-1/6 *2xв квадрате-5/6х=0
умножаем на 6 3*2xв квадрате-xв квадрате-5х-3=0
2 xв квадрате-5х-3=0
Д=25+24=49
х1=-1,5 х2=3
(1-2sin²x)(-sinx+1-2sin²x)=0
cos2x*(2sin²x+sinx-1)=0
cos2x=0⇒2x=π/2+πn,n∈z⇒x=π/4+πn/2,n∈z
n=-1⇒x=-π/2+π/4=-π/4∈[-1,6;0,8]
n=0⇒x=π/4∈[-1,6;08]
2sin²x+sinx-1=0
sinx=a
2a²+a-1=0
D=1+8=9
a1=(-1-3)/4=-1⇒sinx=-π/2+2πk,k∈z
k=0⇒x=-π/2∈[-1,6;0,8]
a2=(-1+3)/4=1/2⇒sinx=1/2
x=π/6+2πm,m∈z
m=0⇒x=π/6∈[-1,6;0,8]
x=5π/6+2πc,c∈z
нет корней на данном промежутке
x={-π/2;-π/4;π/4}